Data resource profile: network for analysing longitudinal population-based HIV/AIDS data on Africa (ALPHA Network) - Reniers,G; Wamukoya,M; Urassa,M; Nyaguara,A; Nakiyingi-Miiro,J; Lutalo,T; Hosegood,V; Gregson,S; Gomez-Olive,X; Geubbels,E; Crampin,AC; Wringe,A; et al. (International Journal of Epidemiology, 2016)
The Network for Analysing Longitudinal Population-based HIV/AIDS data on Africa (ALPHA Network, http://alpha.lshtm.ac.uk/) brings together ten population-based HIV surveillance sites in eastern and southern Africa, and is coordinated by the London School of Hygiene and TropicalMedicine (LSHTM). It was established in 2005 and aims to (i) broaden the evidence base on HIV epidemiology for informing policy, (ii) strengthen the analytical capacity for HIV research, and (iii) foster collaboration between network members. All study sites, some starting in the late 1980s andearly 1990s, conduct demographic surveillance in populations that range from approximately 20 to 220 thousand individuals. In addition, they conduct population-based surveys with HIV testing, and verbal autopsy interviews with relatives of deceased residents. ALPHA Network datasets have beenused for studying HIV incidence, sexual behaviour and the effects of HIV on mortality, fertility, and household composition. One of the network’s substantive focus areas is the monitoring of AIDS mortality and HIV services coverage in the era of antiretroviral therapy. Service use data areretrospectively recorded in interviews and supplemented by information from record linkage with medical facilities in the surveillance areas. Data access is at the discretion of each of the participating sites, but can be coordinated by the network.